The reactivation of Kaposi's Sarcoma-associated Herpesvirus (KSHV) by SARS-CoV-2 in non-hospitalised HIV-infected patients - Lambarey, Humaira (Department of Integrative Biomedical Sciences (IBMS), 2025)
High exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the COVID-19 pandemic, occurred primarily in densely populated, low-income communities which are additionally burdened by a high prevalence of Human Immunodeficiency Virus (HIV) and Kaposi's Sarcoma Associated Herpes Virus (KSHV). SARS-CoV-2 co-infection with herpesviruses has been suggested to have an impact on acute and/or long-term disease progression by triggering their reactivation from latency. We have previously reported that lytic KSHV infection (assessed by blood viral load (VL)) was associated with morbidity and mortality in critically ill COVID-19 patients. However, the impact of SARS-CoV-2 exposure on HIV/KSHV co-infected non-hospitalised individuals is currently unknown. We therefore performed a longitudinal observational cross-sectional study (n = 407) on non-hospitalised HIV-infected adult patients attending antiretroviral therapy (ART) services in Gugulethu, South Africa, from October 2020 to April 2023. The start of recruitment for this study coincided with the decline of SARS-CoV-2 infections from the first COVID-19 wave and before nation-wide COVID-19 vaccine roll-out, continuing throughout subsequent waves and vaccine introduction. Exposure to SARS-CoV-2 was very high and increased from an initial quarterly 76.2 % seropositivity (before COVID-19 vaccine roll-out) to 94.9 % by the end of the recruitment; 32.2 % of this cohort was self-reportedly vaccinated against COVID-19. The overall KSHV seroprevalence was 53.5 %, with the quarterly percentage of patients with detectable KSHV VL in the peripheral blood increasing from 3.3 % to 69.2 %. When assessing SARS-CoV-2 seroprevalence and its potential association with KSHV reactivation, we found that KSHV VL presence was significantly associated with SARS-CoV-2 RBD IgG antibody titres in unvaccinated patients, and logistic regression revealed significantly higher odds of KSHV lytic reactivation in unvaccinated patients who were previously exposed to SARS-CoV-2 (adjusted OR 1.28 [95 % CI: 1.05 – 1.55], p = 0.015), compared to vaccinated patients (adjusted OR 0.83 [95 % CI: 0.67 – 1.02], p = 0.080). In addition, we invited KSHV seropositive patients with or without previous SARS-CoV-2 infection for follow-up (FU) (n = 46) every 6 months over a 12-month period to determine the effect of SARS-CoV-2 infection on lytic reactivation of KSHV. Supporting our observations of the cross-sectional study design, the number of unvaccinated individuals with detectable KSHV VL increased, particularly from the 6- (13.3 %) to 12-month (22.2 %) visit but decreased steadily in the vaccinated patients from initial recruitment (15.8 %) to 12-month FU (0 %). Further analysis using a cox regression model confirmed a higher probability of KSHV detection (as a measure of KSHV reactivation) over time in unvaccinated compared to vaccinated patients in response to SARS-CoV-2 exposure. Moreover, we identified one patient with an unusually high KSHV VL early in the recruitment phase who self-reportedly remained unvaccinated against COVID-19 throughout the study period. This patient was invited for FU visits every 6 months for a total of 2 years and exhibited persistent KSHV viremia, together with increased SARS-CoV-2 and KSHV serology. While non-adherence to TB/HIV treatment, his living circumstances and/or malnutrition may be the cause of his uncontrolled KSHV viremia, other underlying infections and specifically (repeated) SARS-CoV-2 infection may have played contributing roles. Cumulatively, the results of this study indicate a positive association between high SARS-CoV-2 exposure and the risk of KSHV reactivation in unvaccinated HIV-infected patients suggesting that, conversely, COVID-19 vaccination plays a protective role against the downstream effects of SARS-CoV-2 infection that we postulate causes lytic reactivation. As lytic reactivation of KSHV may have long-term consequences, particularly in the context of patients with impaired immune functions, identifying and monitoring patients at risk for KSHV reactivation, prevention of KSHV-associated pathologies and appropriate treatment strategies are therefore important in the post-pandemic era.